Chemical Protein Synthesis Enabled Mechanistic Studies on the Molecular Recognition of K27‐linked Ubiquitin Chains. (25th January 2019) - Pan, Man; Zheng, Qingyun; Ding, Shan; Zhang, Lujia; Qu, Qian; Wang, Tian; Hong, Danning; Ren, Yujing; Liang, Lujun; Chen, Chunlai; Mei, Ziqing; Liu, Lei
Abstract: New synthetic strategies that exploited the strengths of both chemoselective ligation and recombinant protein expression were developed to prepare K27 di‐ubiquitins (diUb), which enabled mechanistic studies on the molecular recognition of K27‐linked Ubs by single‐molecule Förster resonance energy transfer (smFRET) and X‐ray crystallography. The results revealed that free K27 diUb adopted a compact conformation, whereas upon binding to UCHL3, K27 diUb was remodeled to an open conformation. The K27 isopeptide bond remained rigidly buried inside the diUb moiety during binding, an interesting unique structural feature that may explain the distinctive biological function of K27 Ub chains. Abstract : Ligation trifft Expression : Zur Herstellung von K27‐Diubiquitinen wurden neue Synthesestrategien entwickelt, die die Stärken der chemoselektiven Ligation und der rekombinanten Proteinexpression nutzen und mechanistische Studien zur molekularen Erkennung von K27‐verknüpften Ubiquitinketten mittels Einzelmolekül‐Förster‐Resonanzenergietransfer (smFRET) und Röntgenkristallographie ermöglichen.